Contribution of High Viral Loads, Detection of Viral Antigen and Seroconversion to Severe Acute Respiratory Syndrome Coronavirus 2 Infectivity. (24th August 2021) - Buder, Felix; Bauswein, Markus; Magnus, Clara L; Audebert, Franz; Lang, Henriette; Kundel, Christof; Distler, Karin; Reuschel, Edith; Lubnow, Matthias; Müller, Thomas; Lunz, Dirk; Graf, Bernhard; et al.
Abstract: Background: From a public health perspective, effective containment strategies for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) should be balanced with individual liberties. Methods: We collected 79 respiratory samples from 59 patients monitored in an outpatient center or in the intensive care unit of the University Hospital Regensburg. We analyzed viral load by quantitative real-time polymerase chain reaction, viral antigen by point-of-care assay, time since onset of symptoms, and the presence of SARS-CoV-2 immunoglobulin G (IgG) antibodies in the context of virus isolation from respiratory specimens. Results: The odds ratio for virus isolation increased 1.9-fold for each log10 level of SARS-CoV-2 RNA and 7.4-fold with detection of viral antigen, while it decreased 6.3-fold beyond 10 days of symptoms and 20.0-fold with the presence of SARS-CoV-2 antibodies. The latter was confirmed for B.1.1.7 strains. The positive predictive value for virus isolation was 60.0% for viral loads >10 7 RNA copies/mL and 50.0% for the presence of viral antigen. Symptom onset before 10 days and seroconversion predicted lack of infectivity with negative predictive values of 93.8% and 96.0%. Conclusions: Our data support quarantining patients with high viral load and detection of viral antigen and lifting restrictive measures with increasing time to symptom onset and seroconversion. Delay of antibody formation may prolong infectivity. Abstract : In 79 respiratory samples from 59 patients, isolation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) correlated significantly with high viral loads and detection of viral antigen, decreasing significantly 10 days after symptom onset and with detection of SARS-CoV-2 antibodies.